Beyond geopolitics: The case for a free trade accord between Europe and Taiwan - Iana Dreyer; Fredrik Erixon; Hosuk Lee-Makiyama; Razeen Sally (European Centre for International Political Economy (ECIPE), 2010)
This paper weighs the case for a free trade agreement (FTA) between the European Union (EU) and Taiwan. It focuses on the role Taiwan has to play in the EU's economic and geopolitical strategy in Asia. Taiwan is one of the key players in the world's Information and Communication Technology (ICT) supply chains. It is also one of the few liberal democracies in East Asia. As such it deserves closer attention from the EU. But Taiwan has been overlooked in the EU's FTA strategy in Asia. Strengthening EU-Taiwan trade relations, through an FTA or other means, must be seen in the context of Taiwan-mainland China relations. Taiwan is diplomatically isolated, with decades of strained, often hostile, relations with the mainland. That has changed since the election of a KMT government in Taipei in 2008, and a major rapprochement is underway. Both sides have signed an Economic Cooperation and Framework Agreement (ECFA). Will that be a bridgehead to Taiwanese FTAs with key trading partners? Will it open the door to an FTA with the EU? (...)
Keywords: 330; Freihandelszone; EU-Staaten; Taiwan